2021
DOI: 10.7717/peerj.12114
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognosis of CDC45 in cervical cancer based on the GEO database

Abstract: Cervical cancer is one of the most common malignant tumors in women, and its morbidity and mortality are increasing year by year worldwide. Therefore, an urgent and challenging task is to identify potential biomarkers for cervical cancer. This study aims to identify the hub genes based on the GEO database and then validate their prognostic values in cervical cancer by multiple databases. By analysis, we obtained 83 co-expressed differential genes from the GEO database (GSE63514, GSE67522 and GSE39001). GO and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…76 The previous studies found that CDC45 as a proliferation-associated antigen and is associated with the progression of malignant tumors. 77,78 Furthermore, it is associated with prognosis in CC, which also coincides with our F I G U R E 6 PPI network of key genes with two clusters.…”
Section: Discussionsupporting
confidence: 87%
“…76 The previous studies found that CDC45 as a proliferation-associated antigen and is associated with the progression of malignant tumors. 77,78 Furthermore, it is associated with prognosis in CC, which also coincides with our F I G U R E 6 PPI network of key genes with two clusters.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, we reviewed 52 published articles associated with CC infections that provided transcriptome-guided hub proteins (genomic biomarkers) for cross-validation of the proposed key genes and the candidate drug agents. There were 255 hub genes reported in those 52 articles, with 7 hub proteins (AURKA, PCNA, CCNB1, CDC45, MCM2, TOP2A, CDK1) appearing in at least 5 articles ( Table S2 ) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 23 , 24 , 25 , 26 , 27 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Five (AURKA, CCNB1, MCM2, TOP2A, and CDK1) of the seven reported hub proteins were found to be similar to our suggested seven KGs.…”
Section: Resultsmentioning
confidence: 99%
“…Several research groups already published different sets of studied or hub differentially expressed genes (studied/hub-DEGs) associated with CC [ 12 , 13 , 20 , 22 71 ]. Here DEGs indicates the differentially expressed genes between CC and control samples.…”
Section: Methodsmentioning
confidence: 99%
“…As opposed to developing a new drug, repurposing existing drugs for certain conditions might save time and money. By this time, numerous studies have proposed different sets of hub/key-genes to explore molecular mechanisms and pathogenetic processes in CC [19][20][21][22][23][24]. Some of these studies have also been suggested their hub-genes or studied-gene guided candidate drugs for the treatment of CC [23,24].…”
Section: Introductionmentioning
confidence: 99%